Pharmacogenomic Characterization and Isobologram Analysis of the Combination of Ascorbic Acid and Curcumin—Two Main Metabolites of Curcuma longa—in Cancer Cells - Ooko, Edna; Kadioglu, Onat; Greten, Henry J.; Efferth, Thomas (Frontiers in Pharmacology, 2017)
Curcuma longa has long been used in China and India as anti-inflammatory agent to treat a wide variety of conditions and also as a spice for varied curry preparations. The chemoprofile of the Curcuma species exhibits the presence of varied phytochemicals with curcumin being present in all three species but AA only being shown in C. longa. This study explored the effect of a curcumin/AA combination on human cancer cell lines. The curcumin/AA combination was assessed by isobologram analysis using the Loewe additivity drug interaction model. The drug combination showed additive cytotoxicity toward CCRF-CEM and CEM/ADR5000 leukemia cell lines and HCT116p53+/+ and HCT116p53−/− colon cancer cell line, while the glioblastoma cell lines U87MG and U87MG.ΔEGFR showed additive to supra-additive cytotoxicity. Gene expression profiles predicting sensitivity and resistance of tumor cells to induction by curcumin and AA were determined by microarray-based mRNA expressions, COMPARE, and hierarchical cluster analyses. Numerous genes involved in transcription (TFAM, TCERG1, RGS13, C11orf31), apoptosis-regulation (CRADD, CDK7, CDK19, CD81, TOM1) signal transduction (NR1D2, HMGN1, ABCA1, DE4ND4B, TRIM27) DNA repair (TOPBP1, RPA2), mRNA metabolism (RBBP4, HNRNPR, SRSF4, NR2F2, PDK1, TGM2), and transporter genes (ABCA1) correlated with cellular responsiveness to curcumin and ascorbic acid. In conclusion, this study shows the effect of the curcumin/AA combination and identifies several candidate genes that may regulate the response of varied cancer cells to curcumin and AA.